Pharmacokinetic Interaction Study Between Saxagliptin and Omeprazole, Famotidine, or Magnesium and Aluminum Hydroxides Plus Simethicone in Healthy Subjects: An Open‐Label Randomized Crossover Study. Issue 4 (30th November 2018) - Ren, Song; Boulton, David W.
Abstract: Saxagliptin is an orally administered, highly potent, and selective dipeptidyl peptidase‐4 inhibitor for the management of type 2 diabetes mellitus. This study was conducted to determine the effect of magnesium and aluminum hydroxides plus simethicone, famotidine, and omeprazole on the pharmacokinetics of saxagliptin and its active metabolite, 5‐hydroxy saxagliptin. This was an open‐label, randomized, 5‐treatment, 5‐period, 3‐way crossover study in 15 healthy subjects. Mean Cmax of saxagliptin was 26% lower, but AUC was almost unchanged when saxagliptin was coadministered with Maalox Max. Mean Cmax was 14% higher, but AUC was almost unchanged when saxagliptin was coadministered with famotidine. Changes in pharmacokinetics of 5‐hydroxy saxagliptin generally paralleled the changes in saxagliptin. These pharmacokinetic changes were unlikely to be clinically meaningful. Coadministration of omeprazole did not affect saxagliptin Cmax or AUC. Saxagliptin in combination with these medicines resulted in no unexpected safety or tolerability findings in these healthy subjects. No dose adjustment of saxagliptin or separation in the time of saxagliptin dosing is necessary with medicines that raise gastric pH when coadministered with saxagliptin.